Under the crescent moon : Rebellion in Mindanao - Vitug, Marites Dañguilan (Quezon City, Philippines : Ateneo Center for Social Policy [and] Public Affairs Institute for Popular Democracy, 2000)
This story of Mindanao is truly much than a story of war. But war's very persistence on that great island suggets that the peace and progress Minadanaoans crave-Muslims, Christians, and Lumad- cannot be reached without first revisiting the sources of conflict and retracing its tortuous path to the present
In the name of honor? -- PART ONE : When warriors talk peace -- Into the mainstream -- PART TWO : The MILF story -- Gun and olive branch -- Islamic neighbors -- PART THREE : Trouble on the fringe -- Flirting with terrorism -- PART FOUR : Dividing Mindanao -- The peace dividend.
Includes index.
Keywords: MORO NATIONAL LIBEARATION FRONT